1993
DOI: 10.1016/0925-4005(93)80008-y
|View full text |Cite
|
Sign up to set email alerts
|

Extended disjoint principal-components regression analysis of SAW vapor sensor-array responses

Abstract: The application of a disjoint principal-components regression method to the analysis of sensor-array response patterns is demonstrated using published data from ten polymer-coated surface-acoustic-wave (SAW) sensors exposed to each of nine vapors. Use of the method for the identification and quantitation of the components of vapor mixtures is shown by simulating the 36 possible binary mixtures and 84 possible ternary mixtures under the assumption of additive responses. Retaining information on vapor concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Sensor arrays based on acoustic wave vapor sensors were first reported in studies using TSM devices by Carey and coworkers [224][225][226]; and studies using SAW devices by Grate and coworkers [95,218,220]. The approach continues to be pursued by various investigators [199,218,[227][228][229][230][231][232][233][234][235][236] and approaches for designing sensor arrays have been proposed [18,186,226,235,237]. …”
Section: Vapor Sensor Systemsmentioning
confidence: 99%
“…Sensor arrays based on acoustic wave vapor sensors were first reported in studies using TSM devices by Carey and coworkers [224][225][226]; and studies using SAW devices by Grate and coworkers [95,218,220]. The approach continues to be pursued by various investigators [199,218,[227][228][229][230][231][232][233][234][235][236] and approaches for designing sensor arrays have been proposed [18,186,226,235,237]. …”
Section: Vapor Sensor Systemsmentioning
confidence: 99%
“…The results of this analysis demonstrate the potential of the SAW instrument for selective measurement of perchloroethylene among a library set of common vapors and are consistent with more exhaustive studies in which the capabilities of SAW sensor arrays for mixture analysis were characterized. (17,(26)(27)(28)(29)(30)(31)(32)(33)37) The calibration protocols employed for the field study were simplified compared with those used in the laboratory evaluation in order to more accurately reflect the way the instruments would likely be used in practice. The portable GC was pre-and postcalibrated on site using three spiked breath standards having concentrations determined immediately prior to the study using the laboratory reference GC.…”
Section: Field Evaluation Of Saw Microsensor Arraymentioning
confidence: 99%
“…(29) Relative response patterns based on calibration data for the vapor test set are presented in Figure 5 to demonstrate the contributions of the different polymer coatings to the instrument's ability to discriminate among a set of vapors. The response patterns for each of the 11 breath samples were classified using extended disjoint principal components regression (EDPCR) (32,37) and the top three classifications were recorded. Possible classifications included each of the four individual vapors and their binary mixtures.…”
Section: Field Evaluation Of Saw Microsensor Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Responses are rapid and reversible, isotherms are linear over fairly wide ranges of vapor concentration, and responses to vapor mixtures are generally additive Zellers and Han, 1996;Zellers et al, 1995). It has been shown that an array of only 3-6 SAW sensors coated with a diverse set of amorphous polymers can produce characteristic response patterns for identifying and quantifying a large number of individual vapors and the components of various vapor mixtures (Park et al, 1999Cai et al, 2000;Zellers and Han, 1996;Zellers et al, 1993Zellers et al, , 1995Grate et al, 1993;Patrash and Zellers, 1993; al., 1988;Wohltjen, 1984). Previous studies from our laboratory have shown that instrumentation similar to that reported on here can be used for several occupational hygiene applications, including personal exposure monitoring and the determination of solvents permeating through chemical protective clothing Park and Zellers, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%